Influenza and Pneumococcal Vaccination of Healthcare Workers during a Pandemic Reduces the Risk and Severity of COVID-19 in Vaccinated - M. P. Kostinov; N. Yu. Nastaeva; A. E. Vlasenko; A. M. Kostinova; K. V. Mashilov; E. G. Simonova (Эпидемиология и вакцинопрофилактика)
Background. Individuals who were vaccinated against seasonal influenza or had a history of pneumococcal vaccination were found to be less likely to become infected and tolerate COVID-19 more easily. However, it has not been sufficiently studied how vaccination against these infections, carried out during the pandemic period, can affect the incidence of COVID-19.Aims. The purpose of the investigation: to study the effect of vaccination against influenza and pneumococcal infection carried out during the pandemic of a new coronavirus infection on the susceptibility and course of COVID-19 in healthcare workers.Materials and methods. In August- Setempber 2020, after the first rise in the incidence of COVID-19, out of 547 employees (aged 18 to 70 years) of a medical organization (MO), 266 (49%) were vaccinated against influenza (group II, n = 98), pneumococcal infection (group III, n = 60) and combined vaccination (group IV, n = 108), while 281 (51%) remained unvaccinated (group 1). Follow-up period: from September 2020 to March 2021 with the registration of the incidence of acute respiratory infections (ARI) according to primary medical records and the use of PCR methods for SARS-CoV-2, epidemiological and statistical analysis.Results. Two months after the start of the study, the proportion of cases of COVID-19 in the 1st group (unvaccinated) was 5% versus 1% in the 4th group (persons vaccinated with two vaccines), after 4 months – 15% and 5%, respectively, and at the end of observation (166 days) – 16% and 8%, respectively. That is, among unvaccinated individuals, the risk of getting COVID-19 was higher by HR = 2.1 [95% CI: 1.0÷4.7] times. The time between the start of observation and a positive test for COVID-19 in study participants was significantly higher in the 4th group compared to the group I: 106 [60–136] days versus 47 [17–75] days. The distribution of patients with COVID-19 according to the severity of viral pneumonia showed that in unvaccinated patients in most (64%) cases, pneumonia had a moderate to severe course, while in the 4th group of patients with combined vaccination in 100% of cases, mild (p = 0.04 for the entire sample).Conclusions. During the COVID-19 epidemic rises, vaccination against respiratory infections remains relevant, reducing the number of cases, the severity of the coronavirus infection and preventing the occurrence of co-infections.